PROMETHEUS: Long-Term Exacerbation and Mortality Benefits of Implementing Single-Inhaler Triple Therapy in the US COPD Population - Gerard Criner; Fernando Martinez; Hitesh Gandhi; Norbert Feigler; Bruce Pyenson; Matthew Emery; Umang Gupta; Muthiah Vaduganathan (Journal of Health Economics and Outcomes Research)
**Background:** The US population includes 24 million to 29 million people with diagnosed and undiagnosed chronic obstructive pulmonary disease (COPD). Studies have demonstrated the safety and efficacy of single-inhaler triple therapy (SITT) in reducing COPD exacerbations. Long-term population implications of SITT use have not been quantified.